A biofidelic birthing simulator. - Kim, E.J (IEEE Engineering in medicine and biology magazine)
The design, testing, and implementation of a novel birthing simulator (patent pending, 6 September 2005) developed specifically to research the delivery process and improve clinical training in uncommon but inevitable complicated human births is reported on. The simulator consists of a maternal model and an instrumented fetal model that are used in conjunction with an existing force-sensing system and a data-acquisition system. The maternal model includes a bony, rotatable pelvis, flexible legs, and an optional uterine expulsive system. The fetal model, which can be delivered repeatedly through the maternal model, is instrumented with potentiometers to measure neck extension, rotation, and flexion during delivery. Simulation of the brachial plexus within the model fetal neck allows measurement of stretch in those nerves at risk for injury during difficult deliveries. Elements mimic the range-of-motion properties of neonate. Two methods for measuring clinician-applied force during simulated deliveries provide trainees with the real-time assessment of their own traction force and allow researchers to correlate fetal neck motion and nerve stretch parameters with clinician-applied traction. Preliminary testing indicates the system is biofidelic for the final stages of the birthing process and can be used for training and research in obstetrics.